Unpacking "new climate wars": Actors and drivers of conflict in the Sahel - Signe Marie Cold-Ravnkilde; Boubacar Ba (Danish Institute for International Studies (DIIS), 2022)
As violence and insecurity increase and the Sahel situation deteriorates further, understanding the main causes and drivers of conflicts is of growing importance. Recently, the assumption that climate change is causing violence and displacement in the region has become prominent, and this has led to the emergence of notions such as 'climate wars' and 'environmental wars'. This report seeks to nuance this mainstream idea and argues that violence and conflict in the Sahel are caused not by climate change but by the presence of armed groups, jihadist insurgencies and military interventions with diverging political and ideological agendas. While acknowledging that conflicts can be exacerbated by climate change, the report challenges the predominant belief that these changes automatically lead to conflict. Focusing on Mali's epicentre of violence, the Mopti region, the report maps the actors and multiple, intertwined, causes behind the ongoing violence including, but not limited to, the role of the state. It concludes by pointing to the importance of understanding the relationship between climate change and conflict in order to design effective and adapted security, political and development responses, and the need for concerted dialogue with local stakeholders and community representatives as a prerequisite for any attempt to prevent and mitigate effects of climate change in the Sahel.
Keywords: 300